EFFECT OF FICUS RELEGIOSA ON BLOOD GLUCOSE AND TOTAL LIPID LEVELS OF NORMAL AND ALLOXAN DIABETIC RABBITS - Wadood, Noreen; Wadood, Abdul; Nisar, Mohammed (Journal of Ayub Medical College Abbottabad, 2003)
Background:The present study was planned to observe the hypoglycemic effect of the '˜Ficus relegiosa', a traditional medicinal plant. This study was performed to study the possible role of indigenous medicinal plants in the treatment of Diabetes mellitus (type-2) Methods: Normal rabbits were divided into 5 groups (1-5) of six animals each. Group 1 served as control and received 15 ml of water only. Group 2 received tolbutamide 500-mg/Kg body weight. Group 3-5 received the extract of Ficus relegiosa dissolved in 15ml of water in doses of 200 mg/Kg, 250 mg/Kg and 300mg/Kg body weight respectively. The diabetic rabbits were also divided in 5 groups on the same pattern. The blood glucose and total lipid levels were estimated before and 1,2, 3 and 4 hours after the administration of the extract. Results: The extract exerted a significant (P< 0.05) hypoglycemic effect in normal rabbits, which was however short lived. The hypoglycemic effect was not significant (P> 0.05) in alloxan treated rabbits. The extract had no significant effect (P> 0.05) on total lipid levels in normal as well as in alloxan-treated diabetic rabbits. The doses used did not show acute toxicity or result in behavioral changes. Conclusion: From this study it may be concluded that the extract acts by initiating the release of insulin by pancreatic beta cells of normal rabbits.